ANALISIS BERBAGAI METODE IDENTIFIKASI ISOFLAVON: LITERATUR REVIEW - Vriezka Mierza; Fitri Aida; Hajar Hartati; Herdiana Verliani; Nisa Alifia Zahra; Rika Valensia (Journal of Pharmaceutical and Sciences, 2023)
Isoflavone is included in the phytoestrogens, a natural plant substance with a structure similar to 17-β-estradiol. It can bind to estrogen receptors so that isoflavones can prevent or slow down forms of cancer related to Alzheimer's hormones, osteoporosis, and others. Isoflavones are also included in the flavonoids found in fruits such as berries, grapes and are most abundant in soybeans and other nuts. From the literature study that has been conducted, it was found that there are several methods for identifying isoflavone compounds, including HPLC/HPLC, TLC, UV-Vis Spectrophotometry, Mass Spectrophotometry, and others. Of the many types of isoflavones that exist, the most commonly identified isoflavones are genistein and daidzein, which can be found in samples of soybeans, soy milk, and processed tempeh. The isoflavone content identified by each researcher differs in terms of the quantity and type of isoflavone content. This is because in identifying isoflavones, there are factors that influence them. The duration of fermentation has an effect because it is related to the presence of dissolved compounds during the fermentation process, which results in differences in the quantity of isoflavones, besides that the reactive and easily oxidized nature of isoflavones causes isoflavones to bind to other compounds to form new unknown compounds so that isoflavones are no longer identified.